F604S exchange in FIP1L1-PDGFRA enhances FIP1L1-PDGFRA protein stability via SHP-2 and SRC: a novel mode of kinase inhibitor resistance - Gorantla, Sivahari Prasad; Reiter, Andreas (Leukemia, 2015)
FIP1L1-PDGFRA is a constitutively activated kinase described in chronic eosinophilic leukemia (CEL) and hypereosinophilic syndrome (HES). Imatinib is clinically active in FIP1L1-PDGFRA-positive diseases. Using in vitro screening to identify imatinib-resistant mutations, we frequently detected a Phe to Ser exchange at position 604 (F604S) of FIP1L1-PDGFRA alone or in combination with other exchanges. Surprisingly, FIP1L1-PDGFRA/F604S did not increase the biochemical or cellular IC50 value of imatinib when compared with unmutated FIP1L1-PDGFRA. However, FIP1L1-PDGFRA/F604S more efficiently induced growth factor independence in cell lines and primary mouse bone marrow cells. Pulse chase analysis revealed that the F604S exchange strongly stabilized FIP1L1-PDGFRA/F604S. The F604S mutation creates a binding site for the phosphatase domain of SHP-2, leading to lower autophosphorylation of FIP1L1-PDGFRA/F604S. This is associated with a reduced activation of SRC and CBL by FIP1L1-PDGFRA/F604S compared with the unmutated oncogene. As SRC inhibition and knockdown resulted in FIP1L1-PDGFRA stabilization, this explains the extended half-life of FIP1L1-PDGFRA/F604S. Interestingly, FIP1L1-PDGFRA/L629P, a recently identified mutation in an imatinib-resistant CEL patient, also showed protein stabilization similar to that observed with FIP1L1-PDGFRA/F604S. Therefore, resistance mutations in FIP1L1-PDGFRA that do not interfere with drug binding but rather increase target protein stability seem to be one of the drug-resistance mechanisms in FIP1L1-PDGFRA-positive disease.
Gesehen am 14.02.2018